Taming information technology lessons from studies of system administrators - Kandogan, Eser. (Oxford : Oxford University Press, 2012)
This text tells the story of system administration through the narratives of real system administrators. It documents dynamic systems of people and machines, of specialists working together to tame information technology infrastructures, developing their own tools and practices over time to create productive work environments.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Information resources management; Information technology -- Management